2021
DOI: 10.33963/kp.a2021.0159
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality and cardiovascular outcomes in Emery-Dreifuss muscular dystrophy in a long-term follow-up

Abstract: background: Emery-Dreifuss muscular dystrophy (EDMD) is an extremely rare muscular dystrophy due to either emerinopathy (EMD) or laminopathy (LMNA). The main risk for patients is that of cardiovascular complications.Aims: This study aimed to identify predictors of adverse clinical events in patients with EDMD in a long-term follow-up observation.Methods: A total of 45 patients with confirmed EMD or LMNA mutation were included in the study. The relationships between clinical parameters, the overall survival rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A previous single-centre study comparing EMD and LMNA variant-carriers showed an association between LMNA variants and all-cause mortality but did not compare MVA or ESHF outcomes or stratify the cohorts by sex. 21 A single male EMD variant-carrier was reported as having MVA. A second, single-centre and cross-sectional study of male EMD variant-carriers did not report any MVA.…”
Section: Discussionmentioning
confidence: 99%
“…A previous single-centre study comparing EMD and LMNA variant-carriers showed an association between LMNA variants and all-cause mortality but did not compare MVA or ESHF outcomes or stratify the cohorts by sex. 21 A single male EMD variant-carrier was reported as having MVA. A second, single-centre and cross-sectional study of male EMD variant-carriers did not report any MVA.…”
Section: Discussionmentioning
confidence: 99%